Mengukur Integritas Kurilumum Pendidikan Indonesia dalam Menghadapi Era Society 5.0 - Whan Nurdiana; Roni Harsoyo (STAI Ihyaul Ulum Gresik, 2021)
The curriculum is the 'key factor' of education and therefore has an important role in facilitating the process of optimal learning. In addition, the curriculum is also a major component in the success of achieving educational goals. The 2013 curriculum is a renewal curriculum from the previous curriculum and has been implemented in Indonesia since 2013. This article explains how the readiness and reliability of the Indonesian education curriculum in preparing students to be able to read various opportunities and be ready to face the challenges of the era of society 5.0. There is great hope that the substance of the curriculum owned by Indonesia can be relevant to the development of science, technology and social so that educational values ​​can be instilled in students in social life in society in the era of society 5.0 which is conditional on the concept of a human-centered and technology-based society.